2017
DOI: 10.1016/j.ssci.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of best practices for emergency response and recovery at a large hospital: A fire emergency case study

Abstract: This paper illustrates a study conducted into the managerial practices implemented to mitigate the consequences of a major fire emergency and to promptly restore normal business operations at a large pediatric hospital. Stemming from prior research on crisis response and recovery in critical infrastructures, this investigation demonstrates that factors such as the complexity of the underlying stakeholder networks, the vulnerability of the involved actors, and several temporal and spatial constraints, all contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…A study in the United States showed that many patients need constant medical care during relocation,[ 78 ] and in other hand, people who lose their family members or patients amid emergency evacuation will require psychological consulting. [ 55 ] Another study showed that one of the most essential elements of response measures is to prioritize patients for translocation. The results of a study in Japan showed that an inappropriate prioritization can lead to overcrowding in the evacuation route, which slows patient translocation speed and extends the evacuation time.…”
Section: Search Resultsmentioning
confidence: 99%
“…A study in the United States showed that many patients need constant medical care during relocation,[ 78 ] and in other hand, people who lose their family members or patients amid emergency evacuation will require psychological consulting. [ 55 ] Another study showed that one of the most essential elements of response measures is to prioritize patients for translocation. The results of a study in Japan showed that an inappropriate prioritization can lead to overcrowding in the evacuation route, which slows patient translocation speed and extends the evacuation time.…”
Section: Search Resultsmentioning
confidence: 99%
“…The MERS epidemic was a hospital crisis caused by an infectious disease, and the role of nurse managers was critical in this situation. Nevertheless, the search results with the keyword "MERS" revealed research on nurses and isolated persons, such as the turnover intention of cohort-isolated nurses in the MERS epidemic [4], post-traumatic stress factors [5], at-home isolation experience of contacted persons [2], the experience of nurses [18] and medical team [19]. However, research on the experience of nurse managers were hard to find.…”
Section: Introductionmentioning
confidence: 99%
“…They need a longer time to escape or be evacuated to safer place due to their weaknesses and mobility impairments. It has been accepted by many researchers in the field of healthcare facilities that the complexity of functions and services of hospital are due to (1) the availability of vulnerable patients, (2) the presence of potentially hazardous materials and (3) the need for the patients to be consistently assisted (Bongiovanni, Leo, Ritrovato, Santoro, & Derrico, 2017). Therefore, safety against fire in hospital buildings is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…During fire, evacuating patients to a safe place is not only difficult but time-consuming process as well. Therefore, providing a good and sufficient smoke control system should be considered such as adopting Available Safe Egress Time (ASET) when designing hospital (AAMA, 2010).…”
Section: Introductionmentioning
confidence: 99%